The Influence Of Food Quality, Ambiance Condition, And Service Quality On Customer Satisfaction At 5 Star Restaurant And Bar - Kurniawan, Johannes; Then , Julita; Wang, Dicken Sterling; Wibowo, Steven Anthony (Universitas Muhammadiyah Jember, 2024)
This research focuses on analysing the influence of food quality, ambiance conditions, and service quality on customer satisfaction at the fine dining restaurant Alto Restaurant and Bar. The development of the culinary tourism business world which has grown in recent years has made competition increasingly competitive, where customer satisfaction has become an important strategy. This research uses associative quantitative research with the selected unit of analysis being the customers of Alto Restaurant and Bar. The type of sampling used is non-probability sampling with a convenience sampling method. Data collection was carried out by distributing questionnaires via Google form and measuring a 5-point Likert Scale. This research had a total of 112 respondents and the data obtained was analysed using the Structural Equation Modelling method with the SmartPLS 3.0 application. The study's findings underscore the critical importance of prioritizing and continually enhancing service quality in the hospitality industry, while emphasizing the need for businesses to periodically reassess and improve food quality and atmospheric conditions to maintain a well-rounded customer experience.